Application of Discovery Learning Based Video Media In Improving Learning Results Themes 5 Class V SDN Petompon 02 Semester 1 - Ade Febriyanto Wigar (Universitas Sebelas Maret, 2020)
In developing students' potential, the learning process must provide learning experiences for students. In its development the way students learn there are changes according to the times. In the era of the 21st century, all activities in learning involve technology. There needs to be an implementation that is able to provide a learning experience for students as well as provide space for technology in the learning process. This Classroom Action Research consists of two cycles. As subjects in this study were students of class VB SDN Petompon 02 with a total of 37 students. In collecting data on learning outcomes using test and non-test techniques. The instruments used include evaluation questions, assessment rubrics and assessment instruments. The results of the achievement in the first cycle of students completed reaching 24 students with a percentage of 65% and an increase in the second cycle where there were 28 students who completed with a presentation of 78%. The results showed that the use of the Discovery Learning model based on video learning was able to improve learning outcomes in Theme 5 Ecosystems in class VB SDN Petompon 02 Semarang.